Kajian Konservasi Gua Pawon Berdasarkan Kondisi Ekosistem - Deden Rizki Oktaviana; Ina Helena Agustina; Riswandha Risang Aji (UNISBA Press, 2023)
Abstract. Pawon Cave is a natural cave located in the Citatah karst formation area, Rajamandala and is included in the list of geological nature reserves protected by the West Java Provincial Government. Pawon Cave is evidence of the existence of the Ancient Lake Bandung. However, at this time the vulnerability of the cave ecosystem and natural beauty began to change. There is quite an alarming phenomenon where the cave area has begun to be destroyed. It can be seen in the current physical form of the cave, where there is vandalism or there are graffiti on the walls of the cave carried out by irresponsible humans, not only that limestone mining which is currently still taking place in the area is also worrying because it can erode the rocks around the area. The existence of limestone processing also increases air pollution which is getting worse because can be seen that thick black smoke continues to float into the air caused by the processing. Therefore, the purpose of this research is